Pore structure and fractal characteristics of tight sandstone in meandering stream facies: a case study of the J2s2 member in the central Sichuan Basin, China - Feng, Linjie; Jiang, Yuqiang; Guo, Guian; Yang, Changcheng; Zhu, Xun; Zeng, Qinggao; Cai, Guangyin; Wang, Zhanlei (Frontiers in Earth Science, 2023)
Based on porosity and permeability tests, high-pressure mercury injection(HPMI), nuclear magnetic resonance(NMR) and centrifugal experiments, this study comprehensively analyzed the quality, pore structure and fractal characteristics of tight sandstone reservoir in meandering stream facies. The purpose is to reveal the relationship between physical properties, geometry and topological parameters of pores, fluid mobility and heterogeneity of pore system of tight sandstone reservoirs in meandering stream facies. The results show that the second member of the Middle Jurassic Shaximiao Formation (J2S2) in the central Sichuan Basin has developed tight sandstone reservoir of meandering fluvial facies, the pore radius of type I reservoir (K>0.3mD) is mainly distributed at 0.01μm～2μm, the tortuosity ranges between 2.571 and 2.869, and the average movable fluid saturation is 70.12%. The pore radius of type II reservoir (0.08mD＜K＜0.3mD) is mainly 0.003μm～1μm, the tortuosity ranges between 2.401 and 3.224, the average movable fluid saturation is 57.59%. The pore radius of type III reservoir (K＜0.08mD) is mainly 0.001μm～0.4μm, the tortuosity ranges between 0.905 and 2.195, and the average movable fluid saturation is 13.46%. Capillary-Paraachor point (CP point) and T2 cut-off value (T2cutoff) are used to divide the fractal interval of capillary pressure curve and T2 spectrum. The fractal dimension Dh2 of small pores calculated by HPMI through 3D capillary tube model, the fractal dimension Dn1 of large pores and Dn2 of small pores calculated by NMR through wetting phase model can effectively characterize the heterogeneity of reservoir pores. Among them, Dn2 has a strong negative correlation with porosity, permeability, pore radius and movable fluid saturation, indicating that the reservoir capacity, seepage capacity and pore size are mainly controlled by large pores, therefore, Dn2 can be used as an effective reservoir evaluation parameter.